2015
DOI: 10.1155/2016/4202437
|View full text |Cite
|
Sign up to set email alerts
|

SOD2 Mediates Amifostine‐Induced Protection against Glutamate in PC12 Cells

Abstract: Background. Cytoprotectant amifostine attenuates radiation-induced oxidative injury by increasing intracellular manganese superoxide dismutase (SOD2) in peripheral tissue. However, whether amifostine could protect neuronal cells against oxidative injury has not been reported. The purpose of this study is to explore the protection of amifostine in PC12 cells. Methods. PC12 cells exposed to glutamate were used to mimic neuronal oxidative injury. SOD assay kit was taken to evaluate intracellular Cu/Zn SOD (SOD1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In neuronal cells, it can lead to increased ROS and nitric oxide (NO) production, expression of cytotoxic transcription factors, and damaged intracellular Ca 2ϩ homeostasis (excessive Ca 2ϩ influx) (50). Previous studies have addressed the neuroprotective effects of antioxidant enzymes using cell models overexpressing ROS-related enzymes like Cu/Zn superoxide dismutase 1 (SOD1), SOD2, and Prx6 (51)(52)(53). In addition, there are several studies that show that immoderate ROS production is closely related to unstable Ca 2ϩ homeostasis (54).…”
Section: Discussionmentioning
confidence: 99%
“…In neuronal cells, it can lead to increased ROS and nitric oxide (NO) production, expression of cytotoxic transcription factors, and damaged intracellular Ca 2ϩ homeostasis (excessive Ca 2ϩ influx) (50). Previous studies have addressed the neuroprotective effects of antioxidant enzymes using cell models overexpressing ROS-related enzymes like Cu/Zn superoxide dismutase 1 (SOD1), SOD2, and Prx6 (51)(52)(53). In addition, there are several studies that show that immoderate ROS production is closely related to unstable Ca 2ϩ homeostasis (54).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, amifostine could protect rat heart myocytes against doxorubicin [28]. In addition, Jia et al found that amifostine can reduce the apoptosis rate of PC12 cells induced by glutamate [29]. In another investigation, WR-1065, the active form of amifostine, can reduce apoptosis of HL-60 cells induced by etoposide [30].…”
Section: Discussionmentioning
confidence: 99%
“…Once dephosphorylated by the membrane-bound alkaline phosphatase (ALP), AMF is activated to a free thiol form (WR-1065), which is preferentially up taken by normal cells, since ALP is more active and efficiently expressed in normal rather than neoplastic tissue [37]. Moreover, in another study found that WR1065, the active free thiol form of amifostine, induces antioxidative ability against radiation via SOD2 in vitro [38,39]. Other studies have been shown the role of SOD2 in amifostine-induced protective effects, SOD2 mediated amifostine-induced antioxidative actions in PC12 cells exposed to glutamate.…”
Section: Discussionmentioning
confidence: 99%